Application of Artificial Intelligence in detection of diseases in plants: A Survey - et.al, Gyan Singh Sujawat (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The agriculture sector can be considered as the backbone for any developing economy. To obtain the maximum yield from the crops, it is required that farmers should be provided with the best technologies and methodologies. Artificial intelligence is having its vast applications in various sectors. Due to its ability to perceive the problems, developing the appropriate reasons for that and to establish optimal solutions for it, artificial intelligence can act as a great aid in addressing the diseases of crops. The paper presents a brief overview of the application of artificial intelligence in agriculture, its available techniques for agriculture and highlights the various methods available for the detection of diseases in crops